2020
DOI: 10.3390/ijms21165808
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Reveals New Pathway for Cholesterol Egress from the Endolysosomal System

Abstract: In addition to providing invaluable insights to the host response to viral infection, adenovirus continues to be an important model system for discovering basic aspects of cell biology. This is especially true for products of early region three (E3), which have provided the foundation for understanding many new mechanisms regulating intracellular trafficking of host cell proteins involved in the host immune response. Cholesterol homeostasis is vital for proper cellular physiology, and disturbances in cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 110 publications
(142 reference statements)
0
6
0
Order By: Relevance
“…In this case, enteroids have been cultured and infected with rotavirus, and it was observed that the infection by this virus induces an exacerbation of lipid droplets. It was confirmed that the virus takes advantage of the lipogenesis pathways and lipid droplets as structural platforms for virus replication [ 126 ].…”
Section: Role Of Lipid Droplets In the Viral Infection Cycle And Huma...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, enteroids have been cultured and infected with rotavirus, and it was observed that the infection by this virus induces an exacerbation of lipid droplets. It was confirmed that the virus takes advantage of the lipogenesis pathways and lipid droplets as structural platforms for virus replication [ 126 ].…”
Section: Role Of Lipid Droplets In the Viral Infection Cycle And Huma...mentioning
confidence: 99%
“…This has been correlated with elevated levels of total cholesterol, low-density lipoprotein (LDL), and high-density lipoprotein (HDL). This was observed when analyzing serum from AD-5 seropositive individuals using an automated biochemical analyzer and flow cytometry; however, triacylglycerol levels in monocytes derived from AD-5 seropositive individuals were lower compared to control monocytes from AD-5 seronegative individuals [ 27 , 126 ]. This increase in lipoproteins led to an increase in reactive oxygen species (ROS) in addition to activating the innate immune response observed by elevated levels of interleukins and interferons which activated potent antiviral inflammatory responses.…”
Section: Role Of Lipid Droplets In the Viral Infection Cycle And Huma...mentioning
confidence: 99%
See 1 more Smart Citation
“…We had earlier reported that overexpression of human ORP1L in macrophages enhanced atherogenesis in LDL-receptor deficient mice and inhibited macrophage cholesterol efflux [140], consistent with a function of ORP1L in cholesterol trafficking in vivo. Carlin and Manor [141] suggested the intriguing scenario that ORP1L could represent an alternative, under normal conditions tightly regulated cholesterol transport machinery, co-opted upon specific pathologic situations. Examples of this are the endo-lysosomal lipid accumulation upon adenoviral infection that is mitigated by the RIDα-ORP1L route [142], and foam cell formation characterized by excessive cholesterol ester synthesis and storage e.g.…”
Section: Functions Of Orp1 and Orp2 In Vivomentioning
confidence: 99%
“…involves the adenoviral protein RIDa encoded by the early region E3 transcript. This protein attenuates EGFR signalling and dampens pro-inflammatory NF-kB activity induced by the stressactivated EGFR signalling during viral entry [141]. In cells infected with RIDa mutant virus, an NPClike endo-lysosomal lipid storage phenotype arises [142], suggesting that RIDa is required to maintain a normal cholesterol distribution in the infected cells.…”
Section: Other Virusesmentioning
confidence: 99%